The Effect of Inflation, Currency Exchange Rates, BI Rate, Money Supply (M2) on Financial Distress in Banking Companies Listed on the Indonesia Stock Exchange - Fitri Rachmawati Ayuning Tyas; Shinta Permata Sari (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
Companies sometimes experience stages of declining financial condition is defined as financial distress which becomes a signal before bankruptcy occurs. This financial difficulties condition also occurs in banking companies, considering that banking activities are strongly influenced by macroeconomic conditions. Therefore, banking companies must ensure that macroeconomic conditions can be adjusted to the company's operations to create economic’ optimism at large. This study aims to analyze the effect of inflation, currency exchange rates, BI rate, and the money supply (M2) on financial distress. The data is obtained from the annual reports of banking companies listed on the Indonesia Stock Exchange in 2015-2019. Sampling is obtained using the purposive sampling technique with a total of 41 banking companies that meet the criteria. The Hypothesis is tested using multiple linear regression analysis. The test results show the money supply (M2) effects on financial distress. Meanwhile, inflation, currency exchange rates, and the BI rate have no effect on financial distress